THAI TEACHERS’ ATTITUDES TOWARDS ENGLISH AS A LINGUA FRANCA: A LONGITUDINAL STUDY (IAIN Syekh Nurjati Cirebon, 2022)
This study used a longitudinal mixed-method design to investigate how attitudes towards English as a lingua franca (ELF) changed over time as English teachers progressed through education and teaching experiences from 2019 to 2022. An online survey was conducted with 50 Thai teachers in their second year of study and after they graduated and taught at schools for one year. An interview was implemented to collect qualitative data after the two surveys were completed. The survey results indicated a congruent attitude change from ‘agree’ (x̄ = 3.90, S.D. = 0.43) to ‘strongly agree’ (x̄ = 4.22, S.D. = 0.58). The increase was statistically significant (p = .003). The findings revealed controversy between the teachers’ attitudes and their practices. The teachers had positive attitudes towards ELF, but they preferred native speakers’ models of English usage and accents. The interview findings indicated that factors influencing their attitude change were personal factors (e.g., self-perceived English proficiency and exposures to English) and contextual factors (e.g., training and teaching experiences). The findings suggest that awareness of the ELF phenomenon may not be sufficient to drive change in English language teaching (ELT), but ELF-aware teacher education is needed to teach an ELF skillset that best suits the objectives and processes of ELT.